INDUCED OXIDATIVE STRESS BY DEFEROXAMINE (DESFERAL) DURING THE PREGNANCY: PRE AND POST-NATAL DEVELOPMENTAL STUDY - Abeer Thanoon; Ali Alchalabi (Mesopotamia Journal of Agriculture)
The aim of the study is to evaluate the effect of induced oxidative stress by the deferoxamine (desferal) during the pregnancy on pre and post-natal developmen. One hundred twenty adult female albino rats, 3 months old, with an average weight of 175-200 g, were randomly distributed into two main groups (60 rats/group). The 1st (control group) was injected with 0.3 ml physiological salt solution / animal, and the 2nd group was injected with 100 mg deferral/kg B.W. which was given intraperitoneal once daily for three consecutive weeks (during the pregnancy period). At the end of the treatment, each group in turn was divided into two parts, each section comprising 10 animals, blood samples were collected for biochemical analysis, then uterine and fetal tissues collected to observation the studied parameters. Results showed decrease in the numbers of implantation and blastocysts. The number of alive embryos were significantly reduced with an increasing number of dead and reabsorbed embryos, malformation of fetus increase in uterine of the stressed female group compared with control group. Postnatal observations showed significant variations in postnatal development parameters. Our study suggests that the deferral injection has a pro-oxidant capacity on rats' model at dose of 100 mg/kg, and the oxidative stress plays an important role during pregnancy especially on prenatal development as well as persist up to postnatal life.